Behaviour of GFRP-steel reinforced I shape beams with steel fibers as shear reinforcement - Edalat-Behbahani, A. (2019)
This paper evaluates the possibility of developing prefabricated beams without stirrups by using fiber reinforcement for increasing the concrete shear capacity, and a hybrid flexural reinforcement system composed of glass fiber reinforced polymer (GFPR) and steel rebars. A high compressive strength and high post-cracking tensile capacity steel fiber reinforced self-compacting concrete (SFRSCC) was developed, aiming at supressing the need of steel stirrups in this type of beams while providing sufficient ductility for structural applications. The experimental results were analysed in terms of failure mode, deformational and cracking behaviour, as well as load carrying capacity. A constitutive model, capable of simulating three types of material nonlinearities simultaneously in an integration point (IP), was used and its predictive performance was assessed by simulating the experimental tests. The numerical approach was then used to assess the potentialities of this material system and structural concept when applied to relatively large span beams.